Electronic Whorksheet Development Based on ESD (Education for Sustainable Development) Biodiversity Subject - Dina Ayu Kiswandini; Slamet Suyanto; Anggi Tias Pratama; Sugma Rizki Tri Utami Yustisiana (Jurnal Penelitian Pendidikan IPA, 2023)
The learning resources used in the learning process only use print media which is limited and does not attract student motivation in the learning process, for this reason learning media is needed that can stimulate student motivation through electronic media in the form of e-workseet. This study aims to develop education for sustainable development (ESD) based biodiversity e-whorksheets learning media products on biodiversity material for class X SMA. This type of research is development research with the ADDIE model consisting of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. This research produced a development product in the form of an ESD-based biodiversity e-whorksheets which was developed based on an assessment from a class X biology teacher at Kasihan 1 Public High School. E-whorksheet was developed with the help of the liveworksheet application. The validation results from the biology teacher were obtained with a percentage of 3.55 with the category "Very Good" in the presentation aspect, the convenience aspect was 3.40 with the criteria "Very Good", the attractiveness aspect was 3.25 with the criteria "Good".